Letter (copy) : Nora Carrillo: Roberto Carrillo - Citrine, Walter, 1887-1983
026-0032-001 International. WMC/EAB 15th August 1939. Mr. W. Carrillo, 7, Orme Court, LONDON. W. 2. Dear Comrade Carrillo, NORA CARRILLO: ROBERTO CARRILLO I have your letter of the 12th August, and can quite understand your anxiety regarding your two children Nora and Roberto. We are doing everything possible to secure from our Home Office permission for them to come to this country, and have today written a further letter urging that the matter be dealt with as quickly as possible. As soon as we have a reply we will, of course, let you know, but meanwhile we can assure you that we will do our utmost to arrange for you to be re-united with your children. Yours sincerely, General Secretary. 292/946/26/32